Given the function w:
[tex] \displaystyle \large{w(x) = {x}^{2} + 1 }[/tex]
Since we want to find w(x+3), the input would be x+3.
Substitute x = x+3 in.
[tex] \displaystyle \large{w(x + 3) = {(x + 3)}^{2} + 1 }[/tex]
Alternate Solution
The answer above works if you want it in vertex form. For this alternate solution, I will convert the function in standard form.
As we know:
[tex] \displaystyle \large{ {(x + y)}^{2} = {x}^{2} + 2xy + {y}^{2} }[/tex]
Therefore:
[tex] \displaystyle \large{ {(x + 3)}^{2} = {x}^{2} + 2(x)(3) + {3}^{2} } \\ \displaystyle \large{ {(x + 3)}^{2} = {x}^{2} + 6x+ 9}[/tex]
Now for function w:
[tex] \displaystyle \large{w(x + 3) = {x}^{2} + 6x + 9+ 1 } \\ \displaystyle \large{w(x + 3) = {x}^{2} + 6x + 10}[/tex]
Hence: